La música en el desarrollo de las funciones cognitivas en los niños de inicial 2 del Centro de Educación Inicial Safari Kids, Ciudad de Riobamba - Carchi Arias, Valeria Estefany (2023)
This research project's general objective was to analyze music's role in the development of cognitive functions in preschool children at the Safari Kids Early Education Centre in the city of Riobamba. Music raises the potential of infants by being an innovative pedagogical tool that strengthens the educational experience, in addition to maintaining active cognitive functions in school activities such as memory, attention, and concentration, which are fundamental for the timely development of children in their lives. The study is descriptive with an explanatory level of research because it describes, gives reasons, and establishes the relationship that exists between the study variables. The behavior of the 18 children of the initial level 2 was observed using a checklist based on the objectives. As a result, rhythmic and musical activities help to stimulate the development of memory, attention, and concentration as they are playful activities of interest to the infants, as we used striking materials that aroused curiosity and allowed the students to maintain their participation in their school experience, especially in early education.